Auditory Hallucination in Hearing Loss Patient: A Case Report - Cibi Siddarth 1, Aarthi Anbalagan1 , Deepthi Pragadeeswaran1, Krishna Prasanth.B2 , Aravindha Babu.N (Institute of Medico-legal Publications Pvt Ltd, 2020)
Hallucination occurs in different modalities (olfactory, tactile, gustatory, visual, and auditory). Auditoryhallucination is the most common among them. It is a form of hallucination that involves perceiving soundswithout external auditory stimulus. It is most common among people with psychotic disorder (schizoprenia).It is also seen in people with hearing impairment. Hallucinations may also be present in 10–15% of normalhealthy individuals. This case study discuss about an adult female of 88 years who reported with a complaintof auditory hallucination for the past 2 years and focuses on the rehabilitation provided and highlights theuse of amplification devices on tinnitus and similar disorders.